2023
DOI: 10.1021/acsami.2c21188
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Variation Oxygen-Content Vanadium–Oxygen Composite Films with Enhanced Crystallinity and Excellent Durability for Smart Windows

Abstract: Vanadium dioxide (VO 2 )-based smart windows show excellent promise for energy-saving and have been extensively researched. However, for the glass industry-compatible magnetron sputtering process, VO 2 films are difficult to obtain and have homogeneous crystalline state, leaving them lacking the ideal solar modulation (ΔT sol ) and sensitivity (narrow hysteresis loop). More importantly, the instability of VO 2 hinders its commercialization. Multilayer structures have been repeatedly investigated to solve these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Vu et al [182] first formed a unique VO 2 nanorod embedded structure by introducing seeding to guide growth during the reaction sputtering process, and then formed a V 2 O 5 /VO 2 thermochromic composite film (as shown in the Figure 17 g), the presence of V 2 O 5 reduced the lattice mismatch of the amorphous surface of VO 2 crystal and blocked water oxygen, thereby greatly slowing down the oxidation process of VO 2 , and finally tested the life of the smart window was as high as 33 years. Similarly, Li et al [184] designed a V 2 O 3 /VO 2 /V 2 O 5 structure, which also uses the V 2 O 5 layer to hinder the oxidation of VO 2 , and the service life of the window can reach 20 years after accelerated experimental tests. In addition, the use of core-shell coating can greatly slow down the oxidation process of VO 2 and ensure the optical properties of the prepared thin film.…”
Section: Smart Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vu et al [182] first formed a unique VO 2 nanorod embedded structure by introducing seeding to guide growth during the reaction sputtering process, and then formed a V 2 O 5 /VO 2 thermochromic composite film (as shown in the Figure 17 g), the presence of V 2 O 5 reduced the lattice mismatch of the amorphous surface of VO 2 crystal and blocked water oxygen, thereby greatly slowing down the oxidation process of VO 2 , and finally tested the life of the smart window was as high as 33 years. Similarly, Li et al [184] designed a V 2 O 3 /VO 2 /V 2 O 5 structure, which also uses the V 2 O 5 layer to hinder the oxidation of VO 2 , and the service life of the window can reach 20 years after accelerated experimental tests. In addition, the use of core-shell coating can greatly slow down the oxidation process of VO 2 and ensure the optical properties of the prepared thin film.…”
Section: Smart Windowsmentioning
confidence: 99%
“…Similarly, Li et al. [ 184 ] designed a V 2 O 3 /VO 2 /V 2 O 5 structure, which also uses the V 2 O 5 layer to hinder the oxidation of VO 2 , and the service life of the window can reach 20 years after accelerated experimental tests. In addition, the use of core‐shell coating can greatly slow down the oxidation process of VO 2 and ensure the optical properties of the prepared thin film.…”
Section: Progress In Vo2 Applicationmentioning
confidence: 99%
“…[ 5–7 ] Extensive research effort has been put into the development of functional intelligent layers, glazing, and structures, which are made of materials with active and dynamic light modulation characteristics. [ 8–11 ] Recent development of smart window technology can be mainly classified as electro‐, [ 12–16 ] thermo‐, [ 17–19 ] mechano‐, [ 20–22 ] photo‐, [ 23 ] and hydro‐/solvato‐chromism, [ 24,25 ] based on the different stimuli‐responsiveness mechanisms. [ 8 ] However, individual stimulus‐chromism provides limited functionalities for smart windows: most previous works focus on energy‐saving functionality only, [ 8,26 ] while giving less attention to other functionalities such as on‐demand privacy, aesthetic appearance, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The toxic impact of vanadium oxides on living organisms is influenced by different issues such as their solubility, concentration, length of treatment, and the type of treated cells (Xi et al 2019;Xi et al 2021). Vanadium pentoxide-based materials are broadly utilized in industrial products such as gas sensors (Niu et al 2021), solar cells (Costals et al 2021), smart glasses (Ma et al 2008), and smart windows (Li et al 2023). Notably, in situ experiments have demonstrated that paints containing V 2 O 5 NPs might inhibit the biofouling of surfaces in seawater (Natalio et al 2012).…”
Section: Introductionmentioning
confidence: 99%